El medio ambiente: alcances desde la jurisprudencia - Morán Valdez, Marcos Omar (2023)
This article deals with some aspects of the environment and its legal protection from the perspective of the highest courts of justice. In this sense, as an initial approximation, a small development of the importance of the environment in the evolution of human life is made. Likewise, two sentences issued by the Peruvian Constitutional Court, by the Supreme Court of Justice of Peru and by the European Court of Human Rights are discussed, and Advisory Opinion OC-23/17 of the Inter-American Court of Human Rights is also discussed, which allow clarifying concepts such as the environment, constitutional protection of the environment, environmental damage, sustainable development, environmental social responsibility, among others.